Aplicación de contabilidad comercial en “Distribuciones Vega”, ubicado en Lago Agrio, provincia de Sucumbíos, periodo: mayo – junio 2016. - Rodríguez Chaves, Fernanda Karina (2017)
This thesis topic: Application of commercial accounting “DISTRIBUTIONS VEGA”, located in Lago Agrio, Sucumbíos, period: May-June 2016, was developed based on the problems encountered and according to the needs of the store, who lacked basic accounting information to facilitate understanding of economic performance based on reasonable financial statements. The objectives proposed at the beginning of the research work were fully met ; the methodology applied began with the structuring of the initial inventory of property, assets , rights and obligations that allowed the rich heritage of the warehouse, subsequently by recording transactions in the journal and control based on the ledgers such as ; kardex control cards for goods, depreciations , payroll , among others; He came to get the same financial statements were prepared considering the existing accounting standards and tax information that provided reasonable knowledge of the owner . The fulfillment of the objectives set allows to record the economic results of the accounting cycle, as a conclusion highlights the importance of using commercial accounting for knowledge of economic and financial operations; It is necessary to continue with this application since the information will allow the owner to make adequate decisions for the improvement of the business.